AN ANALYSIS OF THE ASSOCIATION BETWEEN SOCIODEMOGRAPHIC FACTORS AND ANXIETY LEVELS IN GENERATION Z - Damayanti, Tetania Evi; Kusumawati, Mira Wahyu; Safitri, Wahyuningsih (Journal of Advanced Nursing and Health Sciences, 2025)
Background: Generation Z refers to adolescents and young adults born between approximately the mid-1990s and the early 2010s. Adolescents experience various physical, psychological, and social changes that increase their risk of anxiety. Anxiety in adolescents can stem from academic pressure, social relationships, family issues, concerns about the future, and parental expectations. Common symptoms of anxiety experienced by adolescents include heart palpitations, difficulty concentrating, chest pain, nausea, and restlessness. Sociodemographic factors shape each individual’s social environment and potentially affect how they respond to stress. In an educational context, untreated anxiety can impact learning, concentration, academic achievement, and even long-term mental health. This study aimed to identify the correlation between various sociodemographic factors and anxiety in Gen Z.Methods: This study is an analytical observational quantitative study with a cross-sectional approach. The population consisted of 321 respondents, with a sample size of 76 selected through stratified random sampling using the Slovin formula. The research instrument was the Beck Anxiety Inventory (BAI), which had been previously validated for its reliability. Data analysis in this study used Spearman’s Rho test.Results: The results of the Spearman’s Rho test for gender with anxiety showed a p value = 0.1 (p < 0.05), economic status with anxiety showed a p value = 0.12 (p < 0.05), and age with anxiety showed a p value = 0.4 (p < 0.05) which means there is a relationship between sociodemographic characteristics and anxiety levels in Gen Z.Conclusion: Sociodemographic characteristics influence the anxiety levels of Generation Z.